Mission (im)possible – le traducteur en tant qu’ambassadeur de l’art - Walkiewicz, Barbara (Studia Romanica Posnaniensia, 2024)
This article introduces the translator involved in the translation of art titles and art albums as an ambassador for art. Given the role of painting titles in the process of interpreting a work of art, but also in identifying it from other art products, the translator, as the artist’s spokesperson, has to perform a number of actions to enable the correct interpretation and identification of the work in the target culture. This is a very arduous and responsible task, which is particularly difficult in times of new media and the unlimited possibilities of digital reproduction and distribution of cultural goods. Based on the examples of translations of the titles of paintings by selected French painters published in Polish-language albums, the author shows the translator’s responsibility for the promotion and, above all, for the protection of the identity and integrity of works of art, especially those that belong to the public domain and are therefore deprived of proper protection.